The mechanism of aerobic exercise in ameliorating glycolipid metabolic disorders in metabolic syndrome rats via the miR-27a-PPARγ pathway - Peiyun Wu; Zhizhuo Wang; Kunhui Li; Yao Gao; Jing Yang; Jinwu Wang; Chunlei Shan; Qi Guo; Han Yang; Juan Wang; Yuanshan Jiang; Cheng Lin (PLoS ONE, 2026)
This study investigated how aerobic exercise improves metabolic disorders in rats with metabolic syndrome (MS) and explored the role of miR-27a in this process. MS was induced by a high-fat and high-sugar diet. After eight weeks of treadmill training, aerobic exercise was found to reduce metabolic abnormalities and decrease elevated miR-27a levels, while increasing the expression of PPARγ and key downstream molecules involved in glycolipid metabolism. Downregulating miR-27a via a viral vector produced benefits similar to those of exercise, and combining miR-27a inhibition with exercise led to further improvement. These results suggested that aerobic exercise alleviates MS-related metabolic disorders partly through suppressing miR-27a and promoting PPARγ signaling, revealing a potential therapeutic target.